PATH-ORDERED PHASE-FACTORS IN SCALAR QUANTUM ELECTRODYNAMICS - Pimentel, B. M.; Tomazelli, J. L. (Kyoto Univ, 1995)
Starting from linear equations for the complex scalar field, the two- and three-point Green's functions are obtained in the infrared approximation. We show that the infrared singularity factorizes in the vertex function as in spinor QED, reproducing in a simple and straightforward way the result of lengthy perturbative calculations.